Object of offensive provided by Art. 181-1 the code of Ukraine about administrative offences «consuming prostitution» - Gabrelyan, Andrey (ScienceRise: Juridical Science, 2020)
As a result of the study, a number of scientific provisions were obtained that are important for the practice of applying the administrative law. Investigating the legal signs of engaging in prostitution, it is necessary to correctly establish the object of this offense, that is, to determine those social relations that are harmed and which are under the jurisdiction of norm 181-1. The article proves the thesis that the generic object of the offense under Art. 181-1 will mainly advocate public health rather than public order and public safety. It is proposed to understand the population health as social relations as a set of favorable conditions for the functioning of a living organism. Attention is focused on the fact that only street prostitution (the lowest type of prostitution) will encroach on public order, when a prostitute person offers his/her services – «advertises him/herself», searches for clients or provides his/her services in public places (entrances, underground passages, parks, squares, etc.). In other cases, these actions take place covertly and in no way can violate public order. On the basis of this, a proposal is made to transfer the corpus delicti «Engaging in prostitution» from Chapter 14 «Administrative offenses infringing on public order and public safety» to Chapter 5 «Administrative offenses in the field of labor protection and public health». After analyzing the scientific works on the issue under consideration, it was found, that public morality in the intimate sphere acts as the direct object of the offense. At the same time, the object of prostitution largely depends on how this phenomenon is perceived in society. If it is negative, then the harm to the immediate object will have a pronounced character, if it is neutral, then prostitution will not harm public morality in the intimate sphere and will not create such a threat